PENGARUH PPL TERHADAP MINAT MENJADI GURU MAHASISWA PENDIDIKAN EKONOMI DI UNIVERSITAS TANJUNGPURA PONTIANAK - Simamora, Elsa Febrianty; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to find out the extent of the effect between field experience practice toward theinterest of being a teacherto the PPAPK Economic Education students in academic year 2014 at Tanjungpura University. The methodÂ  used of this research was descriptive in the form of correlative study. This research had all of the 63 students of PPAPK Economic Education in academic year 2014 at Tanjungpura University as its population.In collecting the data, the researcher used indirect communication and documentary study technique. The tools of data collection used were questionnaire and docummentation. The technique of data analysis was descriptiveand simple regression analysis. Based on the result from the t test that had been done, it hadobtained tvalue > t tablr (6.958> 2000) therefore,Ho was rejected and Ha was accepted which meant there was a significant positive effect between field experience practice toward the interest of being a teacher to the PPAPK economic education students in academic year 2014 at Tanjungpura UniversityPontianak. The result of coefficient of determination was 0,442 which meant the contribution of the effect between field experience practice and the interest of being a teacher had 44,2% meanwhile the rest was 55,8% which was affected by another factor that was not included in this researchÂ Keyword:Field Experience Practice, Interest of Being a Teacher.